Optimasi dan Formulasi Sediaan Antiinflamasi Nano Spray Gel Ekstrak Fermentasi Jahe Merah (Zingiber officinale var. rubrum) - Dewi, Ni Wayan Rika Kumara; Putri, Pande Putu Cintya Wiarni; Artika, Made Prita (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Abstract Red ginger (Zingiber officinale var. rubrum) is one of the herbal plants that has anti-inflammatory activity. This study aims to determine the effect of red ginger fermented extract concentration on the physical quality test of nano spray gel preparation. The research method used was laboratory experimentation including fermentation process, extraction, and preparation of nano spray gel. Fermentation of red ginger powder simplisia using Trichoderma harzianum. Formulation of nano spray gel dosage form with active ingredient of red ginger fermented extract with variation of extract concentration 0% (F0); 0.25% (F1); 0.50% (F2); 0.75% (F3); and 1% (F4). Physical quality evaluation included organoleptic test, homogeneity, pH, viscosity, adhesive spreadability, spray pattern, dry time, percent transmittance and phase separation. The results showed that all formulations had good characteristics. Organoleptic tests met the criteria, all preparations were homogeneous with a pH range of 5.6-5.9, viscosity 1884-513 cps, optimal adhesive spreadability, good spray pattern, dry time less than 5 minutes, percent transmittance 98.8-99.9% and no phase separation. Statistical analysis using ANOVA showed significant differences in viscosity test (p = 0.000), dry time test (p = 0.000) and percent transmittance test (p = 0.000), while pH test (p = 0, 059) did not show significant differences. The conclusion of this study is that the concentration of red ginger fermented extract affects the physical quality of nano spray gel preparations with 1% concentration declared the most optimal. Keywords: red ginger, anti-inflammatory, fermentation, nano spray gel